Intra-Subtype Variation in Enteroadhesion Accounts for Differences in Epithelial Barrier Disruption and Is Associated with Metronidazole Resistance in Blastocystis Subtype-7 - Wu Z. (Public Library of Science, 2018)
10.1371/journal.pntd.0002885